The stars askew - Davidson, Rjurik (New York, NY : Tor, 2016)
With the seditionists in power, Caeli-Amur has begun a new age. Or has it? The escaped House officials no longer send food, and the city is starving. When the moderate leader Aceline is murdered, the trail leads Kata to a mysterious book that explains how to control the fabled Prism of Alerion. But when the last person to possess the book is found dead, it becomes clear that a conspiracy is afoot. At its center is former House Officiate Armand, who has hidden the Prism. Armand is vying for control of the Directorate, the highest political position in the city, until Armand is betrayed and sent to a prison camp to mine deadly bloodstone. Meanwhile, Maximilian is sharing his mind with another being: the joker-god Aya. Aya leads Max to the realm of the Elo-Talern to seek a power source to remove Aya from Max's brain. But when Max and Aya return, they find the vigilants destroying the last remnants of House power. It seems the seditionists' hopes for a new age of peace and prosperity in Caeli-Amur have come to naught, and every attempt to improve the situation makes it worse. The question now is not just whether Kata, Max, and Armand can do anything to stop the bloody battle in the city, but if they can escape with their lives.
"A Tom Doherty Associates book."
Keywords: Fantasy fiction